Synergistic protective effect of N-acetylcysteine and taurine against cisplatin-induced nephrotoxicity in rats - Abdel-Wahab WM; Moussa FI; Saad NA (Drug Design, Development and Therapy, 2017)
Wessam M Abdel-Wahab,1,2 Farouzia I Moussa,2 Najwa A Saad3 1Department of Biology, College of Medicine, University of Dammam, Dammam, Saudi Arabia; 2Department of Zoology, Faculty of Science, University of Alexandria, Alexandria, Egypt; 3Department of Zoology, Faculty of Science, University of Benghazi, Benghazi, Libya Abstract: Cisplatin (cis-diaminedichloroplatinum II; CDDP) is an effective anticancer drug, but it has limitations because of its nephrotoxicity. This study investigates the protective effect of N-acetylcysteine (NAC) and taurine (TAU), both individually and in combination, against CDDP nephrotoxicity in rats. For this purpose, 48 male rats were assigned into eight groups (n=6) as follows: 1) control group, 2) NAC group, 3) TAU group, 4) NAC–TAU group, 5) CDDP group, 6) CDDP–NAC group, 7) CDDP–TAU group, and 8) CDDP–NAC–TAU group. Cisplatin was administered as a single intraperitoneal injection at a concentration of 6 mg/kg. Three days after CDDP administration, NAC (50 mg/kg) and/or TAU (50 mg/kg) were administered three times weekly for four consecutive weeks. Kidney function markers in serum, urinary glucose and protein, as well as oxidant and antioxidant parameters in renal tissue were assessed. Administration of CDDP significantly elevated urinary glucose and protein, as well as serum creatinine, urea, and uric acid. Moreover, CDDP enhanced lipid peroxidation and suppressed the major enzymatic antioxidants in the kidney tissue. Treatment with NAC or TAU protected against the alterations in the serum, urine, and renal tissue when used individually along with CDDP. Furthermore, a combined therapy of both was more effective in ameliorating CDDP-induced nephrotoxicity, which points out to their synergistic effect. Keywords: cisplatin, nephrotoxicity, oxidative stress, N-acetylcysteine, taurine